Assessment of the importance-performance levels of sustainable development indicators in informal settlements (Case study: Koshtargah Neighborhood - Urmia) - Nima Bayramzdeh (طراحی و برنامه ریزی در معماری و شهرسازی)
For various reasons such as providing affordable housing, migration from rural areas, the phenomenon of informal settlements has been expanding and causing numerous problems, such as inadequate access to urban services (educational, health, cultural, etc.), creating an unsightly appearance, reproducing poverty, and decreasing the quality of urban spaces. Among these areas, one of the neighborhoods is the Koshtargah neighborhood, which has an inappropriate situation and has grown on the outskirts of Urmia city, requiring special attention from city managers to prevent the reproduction of inequality. The main goal of this research is to evaluate the importance-performance level of sustainable development indicators in the informal settlement of the Koshtargah located in Urmia city. The present research method is descriptive-analytical and has an applied purpose. Data collection in this research was done both library-based and in the field. The statistical population of this research is the residents of the Koshtargah neighborhood, and with the use of Cochran's formula, the sample size of 375 has been estimated and randomly selected. 10 urban specialists confirmed the validity of the questionnaire, and the reliability of the questionnaires, using Cronbach's alpha test, for 20 questionnaires and a value of 0.727, has been approved. Data analysis was done quantitatively using the importance-performance analysis technique and one-sample t-test. The results of this research indicate that the status of sustainable development indicators in the Koshtargah neighborhood is below the average level by 2.1, and with the examination of the IPA technique, the factors of income satisfaction and access to public transportation are the most important indicators for improving the level of sustainable development in the Koshtargah neighborhood. In general, improving access to public transportation and increasing residents' financial income can significantly improve the level of sustainable development in this neighborhood.